2011
DOI: 10.1002/elps.201000604
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the retention factor for weak acids in micellar electrokinetic chromatography with cationic surfactant via variation of the chloride concentration

Abstract: For tetradecyltrimethylammonium bromide in boric acid/borate or acetic acid/acetate buffer and NaCl or CaCl₂ as the added salt, it is investigated whether the retention behaviour of weak acids in MEKC with cationic surfactant can be modelled by assuming for the deprotonated species predominantly electrostatic interaction with the micelles acting as a pseudostationary ion-exchanger. The retention of (partially) charged solutes by oppositely charged micelles is analyzed by applying the classical theory of IEC (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The effect of the third competing ion manifests itself substantially at low carbonate concentration resulting in a constant plateau value at low c(carbonate), while a linear decrease in lg( k ) is obtained at higher c(carbonate) (influence of bromide ion can be neglected). These observations are in agreement with former reports . Although the maximum slope of the curves does not match with the theoretical value of −1 or −2, Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The effect of the third competing ion manifests itself substantially at low carbonate concentration resulting in a constant plateau value at low c(carbonate), while a linear decrease in lg( k ) is obtained at higher c(carbonate) (influence of bromide ion can be neglected). These observations are in agreement with former reports . Although the maximum slope of the curves does not match with the theoretical value of −1 or −2, Fig.…”
Section: Resultssupporting
confidence: 89%
“…These results are corresponding to what is expected from the classical theory of IEC. In addition, these results support our previously reported results [9,10] that micelles (in case of analytes of opposite charge) can be considered as a pseudostationary ion exchanger. As expected from Eq.…”
Section: Retention Factor Dependent On Competing Ion Concentrationsupporting
confidence: 91%
“…This means that effects due to a longitudinally inhomogeneous EOF can be excluded (we expect the same inhomogeneity in both cases, to a small extent more pronounced in Case D, due to the difference in the ionic strength). According to our results , differences in the ionic strength (accompanied with differences in the electric conductivity) will only have an impact on the sweeping efficiency via decreasing k S at higher ionic strength due to a higher concentration of the competing ion (regarding SDS micelles as pseudostationary ion‐exchanger ). Consequently, the improved enrichment efficiency observed with the sample containing 0.2% v/v triethylamine with a pH adjusted back to pH 2.15 by 1 mol/L phosphoric acid cannot be attributed to a better sweeping efficiency due to an increase in k S .…”
Section: Resultsmentioning
confidence: 70%
“…It can be expected to have a very high retention factor in the sample zone due to the simultaneous strong hydrophobic and electrostatic interaction with the negatively charged outer shell and the hydrophobic micellar core of SDS micelles. Orentaite et al observed about one order of magnitude higher retention factors for the charged species compared to those retention factors obtained for the neutral species during their study of weakly acidic analytes by MEKC with cationic surfactant. Since k S is much higher than k BGE, a marked additional focusing effect because of the RFGE is expected.…”
Section: Resultsmentioning
confidence: 83%
“…At the beginning of the investigation different compoundsdodecanophenone, ␣ tocopherol, vitamin K1, and dodecylbenzene-were employed as possible micellar markers [19]. Dodecanophenone, ␣ tocopherol, and vitamin K1 did not give reproducible migration times of micelle when using BGE composed of phosphate buffer (pH 7.4) and different surfactants (C 14 MImCl, CMC 2.5 mM/3.5 mM in 25 mM phosphate/water, respectively [20]), CTAB, SDS (CMC 3.27 mM in 20 mM phosphate buffer, pH 7.0 [21]) probably due to the strong absorption on the capillary wall and high methanol content needed in the marker sample solution [14,18]. Replacing the phosphate buffer (pH 7.4) with MOPS, TES, and HEPES buffers (pH 7.4) to improve the migration time reproducibility of the mentioned markers did not give any positive results with the same surfactants (C 14 MImCl, CTAB, SDS).…”
Section: Choice Of Micelle Markermentioning
confidence: 99%